Consumer Perceptions and Sustainability Challenges in Game Meat Production and Marketing: A Comparative Study of Slovakia and the Czech Republic - Němec, Martin; Riedl, Marcel; Šálka, Jaroslav; Jarský, Vilém; Dobšinská, Zuzana; Sarvaš, Milan; Sarvašová, Zuzana; Bučko, Jozef; Hustinová, Martina (Foods (Basel, Switzerland), 2025)
Game meat production represents a unique opportunity to align ecological sustainability with the growing consumer demand for sustainable agri-food products. This study focuses on the perspectives of processors and landowners in Slovakia and the Czech Republic, examining their views on market trends, customer behaviours, barriers, and sustainability challenges. Focusing on these key stakeholders, the study highlights their central role as key drivers in shaping and sustaining the game meat value chain. This research combines secondary data analysis and in-depth interviews with key stakeholders to provide a comprehensive understanding of the game meat sector. Findings highlight that, while game meat is valued for its organic and sustainable qualities, barriers such as limited consumer awareness, high costs, and regulatory constraints hinder its market potential. The study reveals the vital role of consumer education, branding, and the development of value-added products in bridging the gap between ecological management and sustainable market growth. Moreover, the research underscores the need for tailored policies to address structural inefficiencies, promote collaboration across the value chain, and enhance accessibility to sustainable game meat products. By aligning production and marketing strategies with consumer preferences, the sector can contribute significantly to sustainable agri-food systems while supporting rural economies and biodiversity conservation. This study provides actionable recommendations for industry stakeholders and policymakers aiming to foster sustainable practices and consumer engagement in the game meat market.
Keywords: Slovakia; sustainable agri-food systems; Czech Republic; game meat production; consumer perceptions; sustainability